Discovered just before extinction? The first endemic ant from the Balearic Islands (Lasius balearicus sp. nov.) is endangered by climate change. (11th November 2014) - Talavera, Gerard; Espadaler, Xavier; Vila, Roger
Abstract: Aim: We analyse the taxonomic status, phylogenetic relationships, distribution and age of a newly discovered ant taxon found in the mountaintops of the island of Mallorca (Spain). We also consider the potential impact of short‐term climate change on the survival of this ant and make proposals on its conservation status, risks and management. Location: Balearic Islands (Spain). Methods: We used morphological, molecular and ecological evidence to assess the specific status of the potential new species. We gathered distribution data to conduct climate‐based distribution modelling of present and future occupancy under several SRES emission scenarios. Results: The existence of a new non‐cryptic species of ant ( Lasius balearicus Talavera, Espadaler & Vila, sp. nov.) is described from the island of Mallorca. Its distribution was found to be extremely restricted (Serra de Tramuntana) and elevationally constrained to island summits (between 800 and 1400 m a.s.l.). Molecular dating indicated that this species diverged about 1.51 million years ago from its nearest relatives, from which it can be distinguished based on several morphological traits. Ecological niche modelling shows a dramatic reduction of areas with suitable climatic conditions under the different scenarios studied. Main conclusions: Lasius balearicus represents the first endemic ant to be described in the Balearic Islands, as well as the first endemic Lasius species in the Mediterranean islands. Distribution modelling predictions, the low intraspecific genetic diversity observed, and the geographical and elevational isolation of the populations indicated a low probability for the survival of the species in the short term, thus making it a potential model to study real‐time climate‐based biodiversity loss. As a consequence, we strongly recommend including L. balearicus in the IUCN Red List of Threatened Species under the category 'Endangered'. This case illustrates that a fraction of biodiversity remains unexplored even within Europe, arguably the best‐studied region of the planet, and that the available time‐window for us to study and protect it may be in some instances notably narrow.